The Nutritional Value of Moringa Plant as a Superfood: A Comprehensive Review - Shadab Ali; Anuradha Singh; Amar Singh Kashyap (International Journal of Sustainability, 2024)
Moringa oleifera, commonly known as the "miracle tree," has garnered global attention for its rich nutritional profile and diverse medicinal properties. This review article comprehensively explores the nutritional composition and health benefits of Moringa, highlighting its potential as a superfood. The plant is rich in essential nutrients, including proteins, vitamins, minerals, and bioactive compounds, such as flavonoids and phenolic acids. These constituents contribute to its antioxidant, anti-inflammatory, antimicrobial, and anti-cancer properties. Moringa also shows promise in managing chronic conditions like diabetes and cardiovascular diseases. Additionally, the plant's various parts—leaves, seeds, pods, and flowers—are used in traditional and modern medicine and culinary applications. Despite its widespread benefits, Moringa's consumption should be moderated, as excessive intake may lead to gastrointestinal issues. This review underscores Moringa's multifaceted role in promoting health and nutrition, making it a valuable subject for further research in the fields of nutrition and medicine.
Keywords: Health; Nutrition; Superfood; moringa; supplements